2020
DOI: 10.3390/vaccines8040772
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Antibodies against SARS-CoV-2 in the Domestic Cat Population of Germany

Abstract: Domestic cats (Felis catus) are popular companion animals that live in close contact with their human owners. Therefore, the risk of a trans-species spreading event between domestic cats and humans is ever-present. Shortly after the emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its rapid spread around the world, the role of domestic cats in the transmission cycle was questioned. In the present study, the first large-scale survey of antibody occurrence in the domestic cat pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
134
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 29 publications
15
134
5
2
Order By: Relevance
“…Both enteric (FECV) and FIP (FIPV) coronavirus seropositive sera showed no cross-reactivity with the SARS-CoV-2 serological test used in this study, as previously shown in studies using the receptor-binding domain (RBD) protein ELISA [ 19 , 21 ], IFAT [ 21 ], VNT [ 24 ] and microsphere immunoassay [ 12 ]. This sero-prevalence study was therefore not affected by feline coronavirus infection, which is endemic in stray cats in Lombardy region of northern Italy, with a seroprevalence of 39% in 82 stray cats captured from courtyards in urban areas of Milan in 2014 [ 35 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Both enteric (FECV) and FIP (FIPV) coronavirus seropositive sera showed no cross-reactivity with the SARS-CoV-2 serological test used in this study, as previously shown in studies using the receptor-binding domain (RBD) protein ELISA [ 19 , 21 ], IFAT [ 21 ], VNT [ 24 ] and microsphere immunoassay [ 12 ]. This sero-prevalence study was therefore not affected by feline coronavirus infection, which is endemic in stray cats in Lombardy region of northern Italy, with a seroprevalence of 39% in 82 stray cats captured from courtyards in urban areas of Milan in 2014 [ 35 ].…”
Section: Discussionsupporting
confidence: 78%
“…However, we did not additionally investigate our samples by other serological methods such as IFAT or VNT, in order to confirm the antibody status and assess the level of neutralizing antibodies in the ELISA seropositive cat. In a previous study the IFAT confirmed the antibody-positive status of the ELISA pre-screened serum samples, but neutralizing antibodies were only detected in 33.3% (2/6) of the ELISA- and IFAT-positive serum samples and titers of the VNT test did not correspond to the OD values of the ELISA test [ 21 ]. This has also been observed in other studies [ 12 , 19 ] and is most likely due to a delayed production of neutralizing antibodies as shown in studies in ferrets in which the neutralizing antibodies appear with a delay of around two weeks after the detection of antibodies by IFAT [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 69 samples for serology originated from dogs (47) and cats (22) from a known COVID-19 affected household and 12.8% (6/47) of these dogs and 4.5% (1/22) of these cats tested positive for SARS-CoV-2-neutralizing antibodies; in addition, the seroprevalence found in dogs from a known COVID-19 positive household was significantly higher than dogs from COVID-19 negative households (1.5%; 2/133) [70]. Along these lines, a German study of 920 serum samples (which had been collected from domestic cats between April and September 2020 for haematological testing) demonstrated that only 0.69% (6/920) of samples contained antibodies against SARS-CoV-2; two of the positive sera had neutralising antibodies [71], suggesting that human-to-cat transmission might be relatively infrequent. Furthermore, a study conducted in a veterinary community of 20 students, two of whom tested positive for COVID-19 and eleven of the remaining 18 displayed symptoms of COVID-19, demonstrated that none of the nine cats and none of the twelve dogs living in the community tested positive by RT-PCR and none of the cats or dogs developed antibodies [72], which confirms that human-to-domestic animal transmission is variable and suggests that transmission is likely minimised where good hygiene is practised.…”
Section: Prevalence Of Sars-cov-2 Infection In Domestic Animalsmentioning
confidence: 98%
“…On March 24 th , the World Organisation for Animal Health reports cases of SARS-CoV-2 infections in cats in 17 countries (USA, China, Belgium, Germany, Spain, France, Russia, United-Kingdom, Japan, Italy, Chile, Brazil, Greece, Canada, Argentina, Switzerland, and Latvia). In the medical and scientific literature, we found 23 papers examining natural SARS-CoV-2 infection in a total of 2242 cats (Barrs et al, 2020; Carlos et al, 2021; Chen, Huang, Zhang, Zhang, & Jin, 2020; Deng et al, 2020; Ferasin et al, 2021; Fritz et al, 2021; Garigliany et al, 2020; Hamer et al, 2020; Hosie et al, 2020; Klaus et al, 2021; Michelitsch, Hoffmann, Wernike, & Beer, 2020; Musso et al, 2020; Neira et al, 2020; Newman et al, 2020; Pagani et al, 2021; Patterson et al, 2020; Ruiz-Arrondo et al, 2020; Sailleau et al, 2020; Segalés et al, 2020; Stevanovic et al, 2020; Temmam et al, 2020; Villanueva-Saz et al, 2021; Zhang et al, 2020). Among these cats, only 94 were positive for ongoing or previous SARS-CoV-2 infection, as detected by qPCR or by serology.…”
Section: Introductionmentioning
confidence: 99%